More to ADHD than meets the eye: Observable abnormalities in search behaviour do not account for performance deficits on a discrimination task - Hall Martin; Elgie Sarah; Sonuga-Barke Edmund JS (Behavioral and Brain Functions, 2005)
Abstract Children with Attention Deficit/Hyperactivity Disorder (ADHD) often perform poorly on tasks requiring sustained and systematic attention to stimuli for extended periods of time. The current paper tested the hypothesis that such deficits are the result of observable abnormalities in search behaviour (e.g., attention-onset, -duration and -sequencing), and therefore can be explained without reference to deficits in non-observable (i.e., cognitive) processes. Forty boys (20 ADHD and 20 controls) performed a computer-based complex discrimination task adapted from the Matching Familiar Figures Task with four different fixed search interval lengths (5-, 10-, 15- and 20-s). Children with ADHD identified fewer targets than controls (p < 0.001), initiated searches later, spent less time attending to stimuli, and searched in a less intensive and less systematic way (p's < 0.05). There were significant univariate associations between ADHD, task performance and search behaviour. However, there was no support for the hypothesis that abnormalities in search carried the effect of ADHD on performance. The pattern of results in fact suggested that abnormal attending during testing is a statistical marker, rather than a mediator, of ADHD performance deficits. The results confirm the importance of examining covert processes, as well as behavioural abnormalities when trying to understand the psychopathophyiology of ADHD.